Pertimbangan Hakim dalam Menjatuhkan Pidana di Bawah Ancaman Minimum Khusus Terhadap Pelaku Tindak Pidana Pencabulan Anak. (Studi Kasus Putusan Pengadilan Negeri Payakumbuh Nomor 120/Pid.Sus/2022) - Khofifah Kusuma Wardani; Ismansyah Ismansyah; Aria Zurnetti (UNES Law Review, 2023)
The norms of judge's consideration are regulated juridically in Article 183 of the Criminal Procedure Code, which states that a judge, when imposing a crime on a defendant, may not impose the crime unless there are at least two valid pieces of evidence, so that the judge has confidence that a crime actually occurred and the defendant is guilty of doing it. The case that often occurs is child molestation as regulated in Article 81 of Law Number 35 of 2014 concerning Child Protection. The purpose of legal regulations regarding child molestation is to protect child victims from perpetrators of these crimes. In its application, discrepancies were found between written legal rules and those applied by judges. Another case of child molestation that occurred and that the author examined was in Payakumbuh, case number 120/Pid.Sus/2022/PN. This is quite unfortunate with the existence of SEMA Number 1 of 2017, because ultimately it is not SEMA that clarifies or provides guidance to Judges, but rather disrupts the legal order and tries to create new norms in the midst of existing norms. The conclusions (1) The judge's considerations from the "justice side" which are guided by SEMA Number 1 of 2017 according to the author have not paid attention to considerations of philosophical, juridical, sociological, educative, preventive, corrective and repressive aspects of imposing a crime below the special minimum for the crime of child molestation. . (2) It is realized that evidence in the form of the defendant's own confession does not always prove the truth. Confession sometimes does not guarantee that the defendant actually committed the act charged. Therefore, the Judge's own confidence is needed. The suggestions that the author makes are (1) Judges in making legal considerations are expected to be able to make them more comprehensively, especially in the case of SEMA Number 1 of 2017. (2) it is recommended that every member of the community take an active role in preventing and dealing with the problem of sexual abuse, such as Immediately report to the authorities if you see and find out.